2020
DOI: 10.1039/d0ra00431f
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-supramolecular complexes from mPEG/PDPA diblock copolymers and their self-assembled strip nanosheets

Abstract: Copolymers mPEG(-b-Tpyp)2-b-PDPAx were synthesized. After a hierarchical pattern from the coordination of the copolymers with Ru(ii) ions followed by the self-assembly in water, 2D strip nanosheets were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…@(-OH) 2 -Br was obtained from the reaction of 1,1,1-tris(hydroxymethyl)propane with 2-bromoisobutyryl bromide (Figure 1R1) and @(-OH) 3 -ene was from the reaction of pentaerythritol with 10-undecenoyl chloride (Figure 1R2). [7] Their 1 H NMR data (Sections S1.2 and S1.3, Figures S1 and S2, Supporting Information) confirmed that they were synthesized successfully. PMPC-SH was synthesized via RAFT polymerization of MPC by using chain transfer agent (CTA) 4-cyano-4-(phenylcarbonothioylthio)pentanoic acid (CPPA) followed by aminolysis of the thiocarbonylthio end group (Figure 1R3).…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…@(-OH) 2 -Br was obtained from the reaction of 1,1,1-tris(hydroxymethyl)propane with 2-bromoisobutyryl bromide (Figure 1R1) and @(-OH) 3 -ene was from the reaction of pentaerythritol with 10-undecenoyl chloride (Figure 1R2). [7] Their 1 H NMR data (Sections S1.2 and S1.3, Figures S1 and S2, Supporting Information) confirmed that they were synthesized successfully. PMPC-SH was synthesized via RAFT polymerization of MPC by using chain transfer agent (CTA) 4-cyano-4-(phenylcarbonothioylthio)pentanoic acid (CPPA) followed by aminolysis of the thiocarbonylthio end group (Figure 1R3).…”
Section: Resultsmentioning
confidence: 62%
“…Then, one alkenyl and two hydroxyl groups were simultaneously added onto PCL 28 3R9). [7] 1 H NMR spectrum of PCL 28 In Figure 4, the resonance at δ = 4.60 (peak j9'') is assigned to the new À C(=O)OCH 2 À group formed via the esterification. The resonances at δ = 8.71 (t5, t1), 8.63 (t4), 8.14 (t7), 7.95 (t3), 7.87 (t6) and 7.34 (t2) ppm assigned to the Tpyp groups could be observed clearly [7] besides the characteristic those of the PCL and PDPA blocks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations